211k views
1 vote
What is the average rate of change from −3 to 0 of the function represented by the graph?

What is the average rate of change from −3 to 0 of the function represented by the-example-1
User Boeprox
by
4.8k points

2 Answers

3 votes

Answer:

What is the average rate of change from −3 to 0 of the function represented by the graph?

m = (f(0) - f(-3)) / (0 - (-3))

m = (0.5 - 2) / (0 + 3)

m = -1.5 / 3

m = -0.5

User Sharma Vikram
by
5.1k points
4 votes

Answer:

Explanation:

Given is a graph of a decreasing function.

We are to calculate the average rate of change from -3 to 0

For this we require f(-3) and f(0)

From the graph we can find the values

f(-3) =2

f(0) =0.50

Change of function from -3 to 0 =


f(0)-f(-3)=0.5-2=-1.5

Change in x value =0-(-3) =3

Average rate of change of function=change in f/change in x value

=
(-1.5)/(3) \\=-0.5

User ForceMagic
by
5.0k points